2022
DOI: 10.1002/jts.22892
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the presence and persistence of posttraumatic stress symptoms following traumatic brain injury in U.S. service members and veterans

Abstract: This study aimed to identify risk factors predictive of the presence and persistence of posttraumatic stress disorder (PTSD) symptom reporting following traumatic brain injury (TBI). Participants were 1,301 U.S. service members and veterans (SMVs) divided into four groups: uncomplicated mild TBI (mTBI; n = 543); complicated mild, moderate, severe, and penetrating TBI (n = 230); injured controls (n = 340); and noninjured controls (n = 188). We examined 25 factors related to demographic, injury-related, military… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Prior studies have highlighted the increased risk of comorbid PTSD and mTBI among military service members compared with civilians. [87][88][89][90] This emphasizes the importance of assessing PTSD symptoms and associated neuropsychiatric symptoms in the management of military-related mTBI. Indeed, while neuroimaging metrics did not show superior discriminatory ability, they did facilitate the JAMA Network Open | Neurology identification of potential lesions associated with neuropsychiatric outcomes, which can be used to predict clinical progression and determine the most suitable treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have highlighted the increased risk of comorbid PTSD and mTBI among military service members compared with civilians. [87][88][89][90] This emphasizes the importance of assessing PTSD symptoms and associated neuropsychiatric symptoms in the management of military-related mTBI. Indeed, while neuroimaging metrics did not show superior discriminatory ability, they did facilitate the JAMA Network Open | Neurology identification of potential lesions associated with neuropsychiatric outcomes, which can be used to predict clinical progression and determine the most suitable treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings were comparable for the single‐item measures of marital stress and family stress versus the multi‐item measure of marital distress, a key agenda item is to capitalize on the superior psychometric qualities of multi‐item measures (e.g., Diamantopoulos et al, 2012). Fourth, we followed the precedent in the literature to operationalize postconcussive symptoms and PTSD symptoms globally (e.g., Agtarap et al, 2019; Lange et al, 2022; McDonald et al, 2021; Stein et al, 2016), but additional research is needed to tie those symptoms to TBI specifically. Finally, the duration of the study was fairly short and concluded 9 months after soldiers returned home from deployment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the duration of the study was fairly short and concluded 9 months after soldiers returned home from deployment. Both postconcussive symptoms (McDonald et al, 2021) and PTSD symptoms (Lange et al, 2022; Lange, Lippa, et al, 2020) can linger for decades after brain injury, so a priority for future work is to track the effects of TBI on marriage over the long term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations